Local strain distribution imaging using terahertz time‐domain spectroscopy. (27th June 2022) - Reig Buades, Luis M.; Karmarkar, Sushrut; Dhiman, Abhijeet; Tomar, Vikas
Abstract: In this work, terahertz time‐domain spectroscopy (THz TDS) was applied to monitor strain distribution as a function of mechanical loading through a passive composite sensor. The composite sensor was made up of strontium titanate (STO) particles. Strain distribution was measured by analysing the change in THz pulse amplitude while it passes through the composite sensor. The change in THz pulse amplitude is related to change in dielectric permittivity. The change in dielectric permittivity induced in the STO composite layer due to deformation leads to a change in the time of arrival (ToA) of the electromagnetic pulse (EMP) in THz band. This change in the sub‐millimetre domain is correlated to the strain and can be mapped for reproducing strain distribution around different geometries. The measurements of strain mapping are compared with finite element simulations and digital image correlation (DIC) measurements, showing similar strain contours.